The effectiveness of the program to prevent children from violence and abuse in increasing awareness of mothers in the issue of violence and abuse: A field study applied to experimental sample of mothers in Riyadh - Al-Mutairi, Amira Suhaili (Journal of Educational and Psychological Sciences, 2018)
The study aimed to identify the effectiveness of the program to prevent children from violence and abuse in raising awareness of mothers. The study used the semi- experimental method. The tool consisted of a questionnaire of (40) paragraphs, applied to a random sample of (20); of the mothers of children in the kindergarten of science and technology in Riyadh, they were divided evenly into 10 experimental groups, ). Using the statistical program (SPSS), the study found the following results: The experimental group obtained a total average of (178.10) compared to the total mean (148.90) for the control group. 80% were familiar with child protection institutions, while the control group was women (Only 20%). In light of the results, the study presented a number of recommendations and proposals, including: Emphasizing the importance of awareness programs, in order to the urgent need of the community for these programs and their role in protecting the child. And the dissemination of parental culture in ways of social upbringing sound for the children to ensure their safety. Fighting poverty and unemployment by supporting charitable institutions, organizing them and activating their role in helping poor families.